2005
DOI: 10.1080/03014460500228741
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of haemoglobin variants in two scheduled tribes of Sundargarh district in north-western Orissa, India

Abstract: Isolates of the Bhuyan and Kharia tribes show intra-group variations in prevalence of haemoglobin variants due to founder effect, genetic drift, and the practice of inbreeding in varied geographical and ecological niches in the Sundargarh district of Orissa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…These two sects of Kharia tribe show the evolutionary trend of the founder effect and/or genetic drift as reported among other populations (Balgir and Sharma 1988). These findings get further support from our earlier studies Balgir 2005a) conducted on this community.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These two sects of Kharia tribe show the evolutionary trend of the founder effect and/or genetic drift as reported among other populations (Balgir and Sharma 1988). These findings get further support from our earlier studies Balgir 2005a) conducted on this community.…”
Section: Discussionsupporting
confidence: 89%
“…The tribe, although originally belonged to one ethnic stock, but now divided into three social groups, namely, the Hill Kharia (Pahari or Paudi), Dudh (Pure) Kharia (converted Christian), and Dhelki (Late Comer) Kharia (Hinduised), and are distinguished from each other on the basis of three grades of primitive culture in the state of Orissa (Balgir 2005a). The Hill Kharia, the primitive and backward section, represents the hunting and food gathering stage of economic life along with the practice of primitive culture and rudimentary shifting cultivation.…”
Section: Background Of Kharia Tribementioning
confidence: 99%
“…It was observed that the frequency of different hemoglobinopathies and G-6-PD deficiency was very high, being 9.8 and 17.0, and 13.3 and 24.9, respectively in the Bhuyan and Kharia tribal communities. [28,29] Since they are endogamous people practicing clan exogamy and area endogamy, the chances of getting these two defects together in an individual is equally high as tribal endogamy leads to increased homozygosity for recessively inherited disorders in malaria endemic populations. High incidence of G-6-PD deficiency has been reported in areas of the Central Eastern India [28] where the different hemoglobinopathies, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Sahu T et al 6 has reported Raita, Sabar, Beera, Mandal, etc tribal community in their study in south Orissa. Balgir R S et al 7 has reported sickle cell disease in Bhuyan and Kharia tribes of north-western Orissa.…”
Section: Discussionmentioning
confidence: 99%